A Report from SEAPEX Evening Talk in Bangkok: Current Understanding of Sundaland Tectonics - Minarwan, Minarwan (Berita Sedimentologi, 2012)
Sundaland, the so called "craton‟ and "stable‟ core of SE Asia, may not be a real craton after all. New granite zircon dating, seismic tomography and heat flow data from the region all point towards relatively young, hot, heterogeneously assembled and easily deformed lithosphere with only local strong crusts. Ongoing research undertaken by Prof. Robert Hall and his team in the Southeast Asia Research Group (SEARG) of Royal Holloway, University of London (UK) shows strong evidences to argue that Sundaland is not a craton and neither are its characteristics similar to well-known cratons such Wyoming (US) and Gawler (South Australia). Their findings were presented by Prof. Hall in a recent SEAPEX Evening Talk that took place on the 31st of July 2012 in Bangkok, Thailand.